High performance computing : second Latin American Conference, CARLA 2015, Petrópolis, Brazil, August 26-28, 2015, Proceedings /: second Latin American Conference, CARLA 2015, Petrópolis, Brazil, August 26-28, 2015, Proceedings. (2015) - Unknown
No abstract available